THE DIAGNOSIS OF SENIOR HIGH SCHOOL CLASS X MIA B STUDENTS MISCONCEPTIONS ABOUT HYDROSTATIC PRESSURE CONCEPT USING THREE-TIER - Wijaya, C. P.; Handayanto, S. K.; Muhardjito, M. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
One of the main problems in physics is the emergence of students’ misconceptions which comes from the prejudices of false starts and a naive belief. Many studies have shown that students tend to have developed their own understanding before the formal teaching is done. The ideas which are developed by students which are different from the explanations by the experts are known as misconceptions. The initial idea that has been formed by the students is very difficult to change by the teachers although the materials are presented with scientific concepts. Misconceptions diagnosis research on the hydrostatic pressure concept was conducted on 23 students of class X MIA B SMAN 3 Malang using Three-tier test. The diagnosis results that the students get misconceptions on the indicators, it explain the hydrostatic pressure is influenced by the depth and at all points located in the horizontal area in the calm liquid has the same hydrostatic pressure, and the hydrostatic pressure is proportional to the density of the fluid, include 1) students believe that hydrostatic pressure is greater at a point closer to the closed cavity (43.5%), 2) the students believe that the hydrostatic pressure is proportional to the density of the submerged object (30.4%), 3) the students believe that the hydrostatic pressure is greater on the outside of the cave because it has a larger volume of fluid so that the pressure is higher (17.4%), 4) students had misconceptions in determining the depth in case of hydrostatic pressure (13%), 5) the students believe that the hydrostatic pressure is greater in the narrow place (13%).